Pengembangan Chatbot Berbasis Dialogflow Dengan Metode Natural Language Processing Untuk Menyediakan Informasi Mengenai Stunting Melalui Platform Telegram - Rahardika, Anindyta Fernanda; Winarno, Edy (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Stunting is a serious problem in children's health in Indonesia, so more in-depth knowledge is needed. Based on the results of the 2019 Ministry of Communication and Information survey, it shows that the Indonesian people have a poor understanding of stunting. A system is needed that can make it easy for the public to get stunting information accurately and quickly, so this research proposes the development of a dialogue-based chatbot that is integrated with the Telegram platform, which can be used as a step to increase public accessibility regarding stunting information. Chatbots are able to effectively assist humans in providing automatic answers to questions from various topics. This research aims to provide stunting information to the public and provide access to stunting information easily and quickly. The stunting information chatbot was developed using the Dialogflow platform by applying natural language processing (NLP) which is integrated with the Telegram application. The chatbot testing results using the black box test obtained an accuracy of 90%, which shows that the output provided by the chatbot is appropriate. The test results using the user experience questionnaire (UEQ) showed that the attractiveness score was 1.80, clarity was 1.17, efficiency was 1.81, decision was 1.74, stimulation was 1.59 and novelty was 1.14.